The efficacy of omega-3 supplements in prevention of preeclampsia among pregnant women with high risk factors in Sulaymaniyah governorate - Yossra Saleh Khudhur; Nabela Kamel Yaquoob; Shaimaa Saleh Khudhur (Tikrit Journal of Pure Science)
Hypertensive disorders of pregnancy, including preeclampsia, complicate up to 10% of pregnancies worldwide, constituting one of the greatest causes of maternal and perinatal morbidity and mortality worldwide. The aim of the current study is to evaluate the efficacy of omega-3 supplements in prevention of preeclampsia among women with high risk. This study was carried out at Shanroy Hospital in al –Sulaimanya city from January 2016 till December 2016.In a single blind clinical trial, a total of 100 pregnant women were divided into two groups, one group had received omega-3 1000 mg and another group receive capsule prefilled with glucose as placebo.